2019
DOI: 10.1248/bpb.b18-00915
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic Effect of Acidic Polysaccharide from <i>Schisandra chinensis</i> on T2D Rats Induced by High-Fat Diet Combined with STZ

Abstract: Polysaccharide is a key bioactive component of Schisandra chinensis and has significant pharmacological activities. The aim of this study was to evaluate the anti-diabetic effect of acidic polysaccharide from Schisandra chinensis (SCAP). Type 2 diabetic (T2D) rats were developed by giving a high-fat diet (HFD) combined with low-dose streptozotocin (STZ), and administered orally with SCAP (25, 50 mg/kg) for 8 weeks. Fasting blood glucose (FBG), fasting insulin (FINS), triglycerides (TG), total cholesterol (TC),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The sample size was calculated using the published data from a previous study [ 19 ] in G-power 3.1, which was performed by including type 2 diabetic patients who were administered a fruit extract for 2 months. The changes in the levels of the main evaluation biomarker (FPG) after 12 weeks of intake in the OSM and placebo groups were assumed as −20.2 and 7.5 mg/dL, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size was calculated using the published data from a previous study [ 19 ] in G-power 3.1, which was performed by including type 2 diabetic patients who were administered a fruit extract for 2 months. The changes in the levels of the main evaluation biomarker (FPG) after 12 weeks of intake in the OSM and placebo groups were assumed as −20.2 and 7.5 mg/dL, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…SCAP treatment has also been reported to prevent drastic loss in body weight in T2D rats. The available data indicate that SCAP imparts a good therapeutic effect in diabetic rats [ 19 ]. Although Omija has been used as a traditional and medicinal plant, there exists only little information on its effect on glycemic control in humans, apart from its high α-amylase and α-glucosidase inhibitory activity, and postprandial plasma glucose-lowering effect both in vitro and in vivo [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings have been previously reported. 36 Study limitations. Short-term GLE therapy for 2 weeks is one of the study's limitations.…”
Section: Impact Of Gle On the Antioxidant Levels In-vivomentioning
confidence: 99%
“…Hong et al stated that Schisandra chinensis fruit-supplemented Korean rice cookie called dasik (RCD) had lipid-lowering and antidiabetic effects [20]. It was found that an acidic polysaccharide from Schisandra chinensis had a therapeutic effect on T2D rats by regulating apoptosis-related protein expression to alleviate the injury from oxidative stress [21]. A water-soluble polysaccharide (SSPW1) from Schisandra chinensis had antioxidant activities and anti-diabetic effect on T2D rats [22].…”
Section: Type 1 Diabetes (T1d)mentioning
confidence: 99%